Faktor-Faktor yang Berpengaruh pada Kematangan Karir Mahasiswa di Era Digital - Jalal, Novita Maulidya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The career maturity of graduates determines their success in working according to their education. Career maturity conditions can show that students have reached career maturity according to the stage of career development. Career maturity is important for students to plan studies and careers that suit their abilities, interests and talents This research aims to find out what factors influence career maturity in students. This research uses a literature study which uses 9 scientific articles with themes related to student career maturity. From the research results, it is known that the factors that influence student career maturity include the dimensions of student attitudes such as work ethic, level of student knowledge and understanding, knowledge of talents and interests, student willingness to compromise regarding the future, student self-confidence, efficacy students themselves, as well as work experience and strength evaluations can predict student career maturity. Furthermore, factors that are considered not influential are student gender and activeness in organizations. The research conclusion is that student career maturity is generally in various categories starting from low to quite high career maturity categories which can be influenced by various factors that influence it. The implications of this research can be used by students as a reference for developing their careers in the digital era